New insights into Wiskott-Aldrich syndrome: ten novel WAS mutations and their clinical impact in a Brazilian cohort - Santos, Lucas W.; Medina, Samuel S.; Frade-Guanaes, Jéssica O.; Siqueira, Lúcia H.; de Lima, Luiz Gustavo R.; Chati, Bruna; Nolasco da Silva, Marcos T.; Riccetto, Adriana G. L.; Lyra, Paula; Falcão, Ana Carla A. M.; Santos, Pedro P. A.; Di Gesu, Regina S. W.; et al. (Frontiers in Immunology, 2025)
BackgroundWiskott-Aldrich Syndrome (WAS) is a rare and severe X-linked immunodeficiency disorder characterized by microthrombocytopenia, eczema, and increased susceptibility to infections, autoimmunity, and malignancies. This study aims to explore molecular changes in the WAS gene in Brazilian patients and assess their correlation with clinical manifestations and disease severity.MethodsThirty-one patients from 27 families with thrombocytopenia suspected to have WAS or X-linked thrombocytopenia (XLT) were analyzed. Clinical evaluation, cell morphology analysis, and flow cytometry (when feasible) were performed. DNA samples underwent direct sequencing to identify WAS gene mutations.ResultsGenomic sequencing identified 17 WAS gene variants, 10 of which were novel, expanding the genetic diversity of the disorder. The most frequent WAS gene variants were primarily frameshift indels that introduced premature stop codons, with five localized in exon 10. While thrombocytopenia and small platelets were prevalent, atypical presentations, including one patient with normal platelet size, were observed. The correlation between genotype and phenotype was complex, as some patients harboring similar mutations demonstrated varying disease severities. Of the 22 confirmed cases, 12 underwent hematopoietic stem cell transplantation (HSCT), while six succumbed to severe disease complications, including opportunistic infections and malignancies.ConclusionsThe study underscores the need for early molecular diagnosis and tailored treatments, particularly HSCT, which remains the standard curative therapy. Additionally, the findings emphasize the role of genetic variation in predicting disease severity, underlining the importance of personalized medical approaches for WAS patients.